The Impact of Transformational Leadership and Organizational Culture on Company Readiness for Digital Transformation: A Case Study of PT Telkom Indonesia - Yudiani, Raden Amanda; Zusnita Muizu, Wa Ode (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
The digital transformation imperative presents unprecedented challenges for state-owned enterprises (SOEs) that must balance public service obligations with market competitiveness. This study aims to examine the relationship between transformational leadership, organizational culture, and digital transformation readiness within PT Telkom Indonesia's Regional II Division. Despite growing literature on digital transformation, research specifically addressing SOEs' transformation challenges remains limited, particularly regarding the interaction between leadership and cultural factors. The study proposes a quantitative approach using stratified random sampling across 16 organizational units, with data collection through comprehensive surveys measuring transformational leadership, organizational culture, and transformation readiness. The research's significance lies in its potential to bridge critical gaps in current literature while providing practical insights for SOEs navigating digital transformation challenges. The findings are expected to contribute to both theoretical understanding of digital transformation in SOEs and practical implementation strategies for organizational leaders.